Identifying Therapeutic Targets for Sepsis Research: A Characterization Study of the Inflammatory Players in the Cecal Ligation and Puncture Model - Nullens, Sara; De Man, Joris; Bridts, Chris; Ebo, Didier; Francque, Sven; De Winter, Benedicte (Mediators of Inflammation, 2018)
During sepsis, disturbed gastrointestinal motility and increased mucosal permeability can aggravate sepsis due to the increased risk of bacterial translocation. To help identify new therapeutic targets, there is a need for animal models that mimic the immunological changes in the gastrointestinal tract as observed during human sepsis. We therefore characterized in detail the gastrointestinal neuroimmune environment in the cecal ligation and puncture (CLP) model, which is the gold standard animal model of microbial sepsis. Mice were sacrificed at day 2 and day 7, during which gastrointestinal motility was assessed and cytokines were measured in the serum and the colon. In the spleen, lymph nodes, ileum, and colon, subsets of leukocyte populations were identified by flow cytometry. Septic animals displayed an impaired gastrointestinal motility at day 2 and day 7. Two days post-CLP, increased serum and colonic levels of proinflammatory cytokines were measured. Flow cytometry revealed an influx of neutrophils in the colon and ileum, increased numbers of macrophages in the spleen and mesenteric lymph nodes, and an enhanced number of mast cells in all tissues. At day 7 post-CLP, lymphocyte depletion was observed in all tissues coinciding with increased IL-10 and TGF-β levels, as well as increased colonic levels of IL-17A and IFN-γ. Thus, CLP-induced sepsis in mice results in simultaneous activation of pro- and anti-inflammatory players at day 2 and day 7 in different tissues, mimicking human sepsis.